2021
DOI: 10.1021/acsinfecdis.0c00826
|View full text |Cite
|
Sign up to set email alerts
|

Retention of 64Cu-FLFLF, a Formyl Peptide Receptor 1-Specific PET Probe, Correlates with Macrophage and Neutrophil Abundance in Lung Granulomas from Cynomolgus Macaques

Abstract: Neutrophilic inflammation correlates with severe tuberculosis (TB), a disease caused by Mycobacterium tuberculosis (Mtb). Granulomas are lesions that form in TB, and a PET probe for following neutrophil recruitment to granulomas could predict disease progression. We tested the formyl peptide receptor 1 (FPR1)-targeting peptide FLFLF in Mtb-infected macaques. Preliminary studies in mice demonstrated specificity for neutrophils. In macaques, 64Cu-FLFLF was retained in lung granulomas and analysis of lung granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Some of them have already been reported. For instance, the roles of PROS1-AXL (34), LAT-TNFRSF1B (35), ANXA1-FPR1 (36,37), MIF-CD74 (38)(39)(40), SPP1-CD44 (41), VEGFB-VEGFR (42), IL6-IL6R (43), and OSM-OSMR (44) have been confirmed in macrophage activation in GBM. Additionally, more novel combinations are first proposed in this work, including TRAIL signaling pathway (TNFSF10-TNFRSF10B), TWEAK signaling pathway (TNFSF12-TNFRSF12A), VISFATIN signaling pathway (NAMPT-(ITGA5+OTGB1)), ncWNT signaling pathway (WNTSA-FZD3), PARs signaling pathway (PRSS3-F2R), and RESISTIN signaling pathway (RETN-CAP1).…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have already been reported. For instance, the roles of PROS1-AXL (34), LAT-TNFRSF1B (35), ANXA1-FPR1 (36,37), MIF-CD74 (38)(39)(40), SPP1-CD44 (41), VEGFB-VEGFR (42), IL6-IL6R (43), and OSM-OSMR (44) have been confirmed in macrophage activation in GBM. Additionally, more novel combinations are first proposed in this work, including TRAIL signaling pathway (TNFSF10-TNFRSF10B), TWEAK signaling pathway (TNFSF12-TNFRSF12A), VISFATIN signaling pathway (NAMPT-(ITGA5+OTGB1)), ncWNT signaling pathway (WNTSA-FZD3), PARs signaling pathway (PRSS3-F2R), and RESISTIN signaling pathway (RETN-CAP1).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if this pattern continued in lung tissue, we stained non-diseased lung tissues from the same animals and found that CD206+ alveolar macrophages were more likely to express IFNλR1 than other immune cells ( Figure 8B ). To refine our understanding of granuloma IFNλR1 expression, we stained FFPE sections for IFNλR1, IFNλ1, and CD163 as a macrophage and ciliated epithelium marker ( 6 , 31 ). In a section where a granuloma was invading an airway and was adjacent to ciliated epithelia, which would be anticipated to express IFNλR1, we noted strong IFNλR1 expression on the apical surface of ciliated epithelial cells ( Figure 8C ).…”
Section: Resultsmentioning
confidence: 99%
“…This was further translated recently in comparison with 2-[ 18 F]F-FDG where [ 64 Cu]Cu-cFLFLF was retained in lung granulomas in MTb-infected cynomolgus macaques. There was a positive correlation with neutrophils and macrophages (and to lesser extent T and B cells) when the granulomas were further analysed (42).…”
Section: Translation Into Work With Tbmentioning
confidence: 89%
“…This could enable the identification of patients who may be at risk of relapsing at the end of their TB therapy and possibly, more importantly, may have a role in identifying those patients with LTBI that may be at risk of developing active disease. As the tracer [ 64 Cu]Cu-cFLFLF in conjunction with 2-[ 18 F]F-FDG has recently been proven utility in the diagnosis and monitoring of TB in cynomolgus macaques (42), it is the hope that this and future work can be translated adequately into the clinical spectrum which will assist in the resolution of many diagnostic dilemmas and challenges within the TB spectrum and thereby make this tracer a suitable option for routine clinical work.…”
Section: Future Perspectivesmentioning
confidence: 99%